Development of the E-SERVQUAL Model for Online Travel Agent to Enhance Customer Experience - Afraah, Sayyidah Maulidatul; Aghniya, Zahwa Putri; Artanto, Brahmastya (TALENTA Publisher, 2025)
The tourism industry in Indonesia plays a crucial role in the national economy. The digital transformation has brought about substantial changes in the tourism sector, particularly in travel agencies. This transformation has led to increased consumer demand for travel services that are easily accessible and reliable. Such demand has been met by the emergence of various Online Travel Agent (OTA) that facilitate the sale of travel-related services through official websites and mobile applications. This study aims to analyze service quality by developing an e-service quality model for the top three OTA with the highest number of users in Indonesia. The limited number of studies specifically addressing service quality models for OTA as urgency of this research. Data collection in this study was conducted through data scraping from the Google Play Store. The research process involved six main stages: data collection, review categorization and mapping, model development, dimensional scoring, result analysis and discussion, and the formulation of solution recommendations. The analysis identified 22 review categories distributed across 8 E-Servqual dimensions. The highest number of reviews was found in the responsiveness dimension, with 114 reviews and an average score of 1.2 out of 5. A more in-depth analysis using the IPA method indicated that the responsiveness and information dimensions were the most frequently reviewed and needed for immediate improvement. Therefore, the study proposes improvements and solution designs to enhance CX through data-driven strategies.